Fabrication and Evaluation of Bilayer Floating Tablet Containing Conventional Ibuprofen and Modified Release Pregabalin for Combination Pharmacotherapy of Neuropathic Pain - Kamble, Santosh R. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The objective of proposed study was to prepare bilayer floating tablet comprising ibuprofen (IB) and pregabalin (PGB) for effective treatment of neuropathic pain. Materials and Methods: IB was formulated as immediate release (IR) layer using disintegrants such as croscarmellose sodium (CCS) and sodium starch glycolate (SSG) whereas PGB was formulated as sustained release (SR) layer using polymers hydroxypropyl methylcellulose (HPMC) K100M, HPMC K4M, sodium alginate and for increasing gastric residence time sodium bicarbonate as gas generating agent, with a view to deliver the drug at sustained manner in gastrointestinal tract and consequently into systemic circulation. Tablet blends were evaluated through various pre-compression tests, compressed by wet granulation method and evaluated. Results and Discussion: As fast disintegrant, SSG at 20% concentration produced excellent results by immediately releasing IB to exert its anti-inflammatory analgesic and other additional beneficial effects. K100M grade of HPMC produced excellent SR efficiency at 1:1 drug-polymer ratio whereas sodium bicarbonate based CO2 gas generating system provides required extended gastric retention of the dosage form for long-lasting effect of the therapeutic agent. Final formulation released 96% drug in 15 min and 98% drug in 24 h, in vitro from respective layers. Conclusion: Pre-compression and post-compression parameters of optimized IR layer comprising IB and floating SR layer comprising PGB exhibit satisfactory results. Bilayer tablet of IB and PGB may prove to be very effective as a combination therapy for the treatment of neuropathic pain by sequential release of the drug.